(untitled) (Arquivos em Odontologia, 2024)
Aim: To evaluate the antimicrobial effect of resveratrol on the bacterium S. mutans. Methods: In the execution of the study, samples were cultured on petri dishes plated with Mueller-Hinton Agar, containing sterile 6 mm diameter Blank discs (Cecton). The discs were soaked with 10 μl of negative control (phosphate-buffered saline - PBS), positive control (0.12% chlorhexidine), and different concentrations of resveratrol (100 μg/mL, 200 μg/mL, 400 μg/mL, and 800 μg/mL). The tests were performed in triplicate, totaling 18 analyses. Results: After 24 hours of incubation, the halos were evaluated and measured using a digital caliper. The data collected were processed statistically using the Anova way program. The diameter measurement for the positive control halo was 2.84 cm; for the resveratrol at 800 μg/mL, it was 0.6 cm; at 400 μg/mL, it was 0.42 cm; and at 200 and 100 μg/mL, it was zero. Conclusion: Resveratrol did not demonstrate efficiency against the bacteria when compared to the negative control (PBS). According to literature, resveratrol produces an antibacterial activity, although its optimal concentration for inhibitory effect is not yet well established.